Mechanical Properties And Thermal Characteristics Of Sandwich Composite Panel From Spent Mushroom Substrate And Empty Fruit Bunch Fibers Towards Heat Insulation Application - Khir, Mohammad Aliff Shakir Mohamad Jamil (2022)
The growing demand for eco-friendly products and materials has prompted several studies on the potentials of natural waste fiber such as coconut husk and sugarcane bagasse as composite panels towards heat insulation application. However, research on composite panels fabricated of the spent mushroom substrate (SMS) and empty fruit bunch (EFB) fibers for insulating purposes is limited properties and thermal characteristic, controlled by a range of parameters. Thus, only a few research have looked at the impact parameters of fiber ratio and fibrillation degree. There are less researcher concentrated on the fabrication process using sandwich composite approach. Therefore, this study aimed to characterize the physico-chemical properties of SMS and EFB fibers towards sandwich composite panel fabrication process; to evaluate the properties and thermal characteristic of the sandwich composite panel at different SMS and EFB fibers ratios and; to assess the effect of EFB fiber fibrillation degree on its properties and thermal characteristic. To achieve these objectives, the SMS and EFB fibers physico-chemical properties in terms of chemical composition, particle size and thermal degradation temperature were characterized and compared with fresh rubberwood sawdust (FRS) fiber